Genetic correlates of olanzapine-induced weight gain in schizophrenia subjects from north India: role of metabolic pathway genes. (August 2008) - Srivastava, Vibhuti; Deshpande, Smita N; Nimgaonkar, Vishwajit L; Lerer, Bernard; Thelma, BK
Aim: Olanzapine is an efficacious drug often used as a first-line medication in the treatment for schizophrenia. However, weight gain is a notable adverse drug reaction of this medication in a proportion of patients and a major cause of noncompliance. Several hypotheses, including a contribution from hormonal, physiological and environmental factors, have been postulated. In this study, we aimed to analyze a possible association of genetic polymorphisms at four important candidate genes involved in appetite regulation and antipsychotic-induced metabolic syndrome with olanzapine-induced weight gain.Materials & methods: A total of 154 schizophrenia subjects were recruited in a systematic, 6-week, open-label trial of olanzapine. We investigated the contribution of 14 polymorphisms from four genes, namely, leptin, lipoprotein lipase, tri-acyl-glycerol lipase and citrate lyase using a binary logistic regression analysis towards olanzapine-induced weight gain.Results: rs 4731426 C/G SNP, a variant in the leptin gene, was moderately associated with median weight gain (ΔΔ weightm ; [p = 0.05; OR: 2.2; 95% CI: 0.99––4.90]) and significantly associated with extreme weight gain (ΔΔ weighte [p = 0.019; OR: 11.43; 95% CI: 1.49––87.55]) when average drug dose was included in a regression model. Using in silico analysis, we found that this associated intronic SNP in the leptin gene alters the binding of zinc finger 5, a transcription factor.Conclusion: The leptin gene may be a promising candidate for olanzapine-induced weight gain. As the associations are modest, replicate studies are warranted. This approach may facilitate rationalized drug regimens.